New phytoconstituents from the aerial parts of Fumaria parviflora Lam - Mohammad Jameel; Abuzer Ali; Mohammed Ali (Wolters Kluwer Medknow Publications, 2014)
Fumaria parviflora Lam. (Fumariaceae) is an annual herb found throughout the world. Traditionally it has great significance in various disorders. In folk medicine of Turkey it is used against hepato-biliary dysfunction and imported from Iran. In Charaka and Sushruta, it is recommended for treatment of fevers, blood disorders, chronic skin diseases, urinary diseases and cough. The compounds were isolated from methanolic extract of the plants by column chromatography using silica gel (60-120 mesh) as stationary phase and structure of the isolated compounds have been established on the basis of spectral data analysis and chemical reactions. Phytochemical investigation of its aerial parts led to the isolation of five new compounds characterized as (5αH,11αH)-8-oxo-homoiridolide (1), n-docosanyl-2-O-β-D-glucopyranosyl salicylate (2), 2-methyl-6-hydroxymethylenedodecan-10-oyl-12, 15-olide14-O-β-D-xylopyranoside (3), 4-oxo-stigmast-5-en-3β-ol-D-glucopyranoside (4) and salicylic acid-O-β-D-xylopyranoside (5) along with the known compounds α-D-glucopyranosyl hexadecanoate (6) and α-D-glucopyranosyl- (2 → 1ʹ)-α-D-glucopyranoside (7). The isolated compounds are useful as they will provide essential data and information for the further researchers and development of effective analytical marker for identity, purity and quality control of this traditional plant in future.